Targeting Autophagy in Thyroid Cancer: EMT, Apoptosis, and Cancer Stem Cells - Holm, Tammy M.; Yeo, Syn; Turner, Kevin M.; Guan, Jun-Lin (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a highly conserved recycling process through which cellular homeostasis is achieved and maintained. With respect to cancer biology, autophagy acts as a double-edged sword supporting tumor cells during times of metabolic and therapeutic stress, while also inhibiting tumor development by promoting genomic stability. Accumulating evidence suggests that autophagy plays a role in thyroid cancer, acting to promote tumor cell viability and metastatic disease through maintenance of cancer stem cells (CSCs), supporting epithelial-to-mesenchymal transition (EMT), and preventing tumor cell death. Intriguingly, well-differentiated thyroid cancer is more prevalent in women as compared to men, though the underlying molecular biology driving this disparity has not yet been elucidated. Several studies have demonstrated that autophagy inhibitors may augment the anti-cancer effects of known thyroid cancer therapies. Autophagy modulation has become an attractive target for improving outcomes in thyroid cancer. This review aims to provide a comprehensive picture of the current knowledge regarding the role of autophagy in thyroid cancer, focusing on the potential mechanism(s) through which inhibition of autophagy may enhance cancer therapy and outcomes.